PEMBUATAN PLATFORM DIGITAL UNTUK EDUKASI DAN E-COMMERCE HIDROPONIK BERBASIS BUSINESS INTELLIGENCE: STUDI KASUS HYDROSPACE - Nurrizkyta Aulia Hanifah; Muhammad Aqil Musthafa Arrachman Musthafa Arrachman; Muhammad Fillah Al Fatih; Nasywa Shafa Salsabila; Gema Parasti Mindara; Aditya Wicaksono (Djtechno: Jurnal Teknologi Informasi, 2025)
Urban farming has become one of the solutions to address limited land availability in cities, with hydroponics being an effective method. However, the low literacy level of the public regarding hydroponics hinders the adoption of this technology. This research aims to develop a digital platform, HydroSpace, which integrates hydroponic education and e-commerce services to facilitate the public's access to information and hydroponic supplies. The Waterfall method was used in the platform's development, focusing on educational features in the form of video tutorials, a hydroponic product marketplace, and a Business Intelligence (BI) system for user data analysis. Data was collected through platform testing with various users, and the results show that HydroSpace effectively improved users' understanding of hydroponics and facilitated the purchase of hydroponic supplies. The conclusion of this research is that HydroSpace can be an efficient solution to enhance hydroponic literacy and support sustainable urban farming.